2019
DOI: 10.1111/iwj.13119
|View full text |Cite
|
Sign up to set email alerts
|

Autologous lipotransfer for bone defects secondary to osteomyelitis: A report of a novel method and systematic review of the literature

Abstract: Autologous bone grafting is the gold standard in patients with bone defects but is associated with significant pain and donor site morbidity. Autologous lipotransfer (fat grafting or lipofilling) has become very popular in the therapy of chronic wounds. Mesenchymal stem cells from adipose tissue are known for their regenerative, reparative, and immunomodulatory effects. This case study and review evaluates the use of autologous lipotransfer for chronic osteomyelitis in a 26‐year‐old patient. A 26‐year‐old fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…24 In a recent case study, AFT was suggested as a filler material for bone cavity defects after debridement due to osteomyelitis. 25 Since AFT remains a nonvascularized transplant, defect size plays a dominant role in these considerations. 26,27 Furthermore, a positive effect of AFT on the patient's pain level during the hospital stay was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a recent case study, AFT was suggested as a filler material for bone cavity defects after debridement due to osteomyelitis. 25 Since AFT remains a nonvascularized transplant, defect size plays a dominant role in these considerations. 26,27 Furthermore, a positive effect of AFT on the patient's pain level during the hospital stay was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, the autologous bone transplantation has been the gold standard for treating large bone defects due to its lack of immunogenicity, excellent osteoinductive, and osteogenic properties 3 . However, the limited sources and donor complications limited its wide application 4 . Recently, the metal implants have been widely applied in orthopedic surgeries, especially for arthroplasty and arthroplasty revision surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the use of simple WAT for clinical purposes is not subject to such strict legal restrictions in most countries, as long as it is used as an unpurified autologous lipo-transfer. Current clinical applications include scar treatment, breast reconstruction after breast cancer surgery, aesthetic rejuvenation, cleft-lip repair and liposculpture for body deformities [30,[33][34][35][36]. The treatment of bone defects, osteomyelitis or chronic wounds is being debated [13,30,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%